The ICE conditions of contract, seventh edition - Eggleston, Brian (Brian C); Eggleston, Brian (Brian C). (Oxford ; Malden, MA : Blackwell Science, 2001)
The ICE Conditions continues to be the dominant form of contract for civil engineering, despite the growing importance of the New Engineering Contract. The Seventh Edition of the ICE Conditions, published in 1999, introduced a number of changes, including:? incorporating some of the concepts of the Latham Report? amending certain provisions of the Sixth Edition which had attracted criticism? rectifying conspicuous omissions from the text of earlier editions of the contract? correcting small errors and faults from the previous edition? modernising certain.
9.3 Impossibility generally9.4 Work to be to the satisfaction of the engineer; 9.5 Mode and manner of construction; 9.6 Delay and extra cost; 10 Programmes and methods of construction; 10.1 Introduction; 10.2 Programmes and method statements generally; 10.3 Clause 14 programmes; 10.4 Clause 14 method statements; 11 Supervision, setting-out and safety; 11.1 Introduction; 11.2 Contractor's superintendence; 11.3 Removal of contractor's employees; 11.4 Setting-out; 11.5 Boreholes and exploratory excavations; 11.6 Safety and security; 12 Care of the works and insurances; 12.1 Introduction
Includes index.
Revised edition of: The ICE conditions of contract, sixth edition: a user's guide / Brian Eggleston. 1993.
Print version record.
John Wiley and Sons
Keywords: Civil engineering contracts -- Great Britain; x; Civil engineering contracts; Great Britain